Why Language Matters: A Qualitative Inquiry Into the Implications of Language Used During Provider-Patient Interactions on University Students’ Perceptions and Understandings of Their Own Mental Health - Colbert Elizabeth Jane; Powell Lauren (Psychology of Language and Communication, 2025)
Language surrounding mental health has been utilised to mechanise and normalise stigma. Associated connotations of prejudice can deter individuals from accessing critical support. There are few studies investigating use of language within clinical contexts. This paper investigates implications of language used during provider-patient interactions in shaping patients’ understandings of their mental health. Semi-structured, online interviews were conducted with ten university students with previously obtained mental health diagnoses or treatment. Interpretative phenomenological analysis identified three core themes: impact of navigating complex language and services on diagnostic experiences; a lack of person centred care as dehumanising; existing prejudices of the individual and others impact experiences of ill mental health. Results suggested clinical language can be emotive, acting as either a barrier or enabler to sense making of mental health diagnoses. This research can translate to operational language use guidelines in clinical settings, ultimately contributing to patient well-being.